N is the number
divided by 6 then n/6
5 was taken away so (n/6)-5
the result is multiplied by 2 so 2((n/6)-5)
result is -12
-12=2((n/6)-5)
divide both sides by 2
-6=(n/6)-5
add 5
-1=n/6
times 6
-6=n
da number was -6
Answer:
B. 91 degrees
Step-by-step explanation:
supplementary angles = 180 degrees, so 180-89 = 91
GIVEN:
We are given the following polynomial;
![x^3+x^2+4x+4](https://tex.z-dn.net/?f=x%5E3%2Bx%5E2%2B4x%2B4)
Required;
We are required to factorize this polynomial completely.
Step-by-step explanation;
To factorize this polynomial, we start by grouping;
![(x^3+x^2)+(4x+4)](https://tex.z-dn.net/?f=%28x%5E3%2Bx%5E2%29%2B%284x%2B4%29)
We now take the common factor in each group;
![\begin{gathered} x^2(x+1)+4(x+1) \\ \\ (x^2+4)(x+1) \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20x%5E2%28x%2B1%29%2B4%28x%2B1%29%20%5C%5C%20%20%5C%5C%20%28x%5E2%2B4%29%28x%2B1%29%20%5Cend%7Bgathered%7D)
Next, we factorize the first parenthesis. To do this we set the equation equal to zero and solve for x as follows;
![\begin{gathered} x^2+4=0 \\ \\ Subtract\text{ }4\text{ }from\text{ }both\text{ }sides: \\ \\ x^2=-4 \\ \\ Take\text{ }the\text{ }square\text{ }root\text{ }of\text{ }both\text{ }sides: \\ \\ x=\pm\sqrt{-4} \\ \\ x=(\pm\sqrt{-1}\times\sqrt{4}) \\ \\ x=\pm2i \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20x%5E2%2B4%3D0%20%5C%5C%20%20%5C%5C%20Subtract%5Ctext%7B%20%7D4%5Ctext%7B%20%7Dfrom%5Ctext%7B%20%7Dboth%5Ctext%7B%20%7Dsides%3A%20%5C%5C%20%20%5C%5C%20x%5E2%3D-4%20%5C%5C%20%20%5C%5C%20Take%5Ctext%7B%20%7Dthe%5Ctext%7B%20%7Dsquare%5Ctext%7B%20%7Droot%5Ctext%7B%20%7Dof%5Ctext%7B%20%7Dboth%5Ctext%7B%20%7Dsides%3A%20%5C%5C%20%20%5C%5C%20x%3D%5Cpm%5Csqrt%7B-4%7D%20%5C%5C%20%20%5C%5C%20x%3D%28%5Cpm%5Csqrt%7B-1%7D%5Ctimes%5Csqrt%7B4%7D%29%20%5C%5C%20%20%5C%5C%20x%3D%5Cpm2i%20%5Cend%7Bgathered%7D)
Therefore, the factors of the other parenthesis are;
![(x+2i)(x-2i)](https://tex.z-dn.net/?f=%28x%2B2i%29%28x-2i%29)
Therefore, the complete factorization of the polynomial is;
ANSWER:
![(x+1)(x+2i)(x-2i)](https://tex.z-dn.net/?f=%28x%2B1%29%28x%2B2i%29%28x-2i%29)
Option C is the correct answer.
Answer:
C 120
Step-by-step explanation:
I believe the answer is 4.4